Pioneering Maintenance Strategies for Enhanced Reliability of Low Voltage Switchboards: Merintis Strategi Pemeliharaan untuk Meningkatkan Keandalan Switchboard Tegangan Rendah - Shobah, Moh. Nurus; Anshory, Izza (Procedia of Engineering and Life Science, 2024)
This study highlights the critical need for rigorous maintenance protocols, focusing on routine inspections, preventative measures, and timely corrective actions. Low voltage switch panels (PHB-TR) are vital for ensuring the efficiency and reliability of electricity distribution systems. Through systematic analysis of existing maintenance procedures and field evaluations across diverse setups, the research confirms that structured maintenance not only mitigates the risk of failures but also significantly reduces workplace accidents. The findings advocate for strict adherence to standard operating procedures and improved coordination among technicians, suggesting these strategies as global standards for enhancing the safety and functionality of electrical distribution networks. Highlights: Proper maintenance ensures optimal performance and reduces the risk of system failure. Adherence to applicable SOPs is crucial to prevent work accidents. Coordination and adherence to job distribution streamline work execution. Keywords: PHB-TR Maintenance, Split Switch Panel Maintenance, Low Voltage Split Switch Board